The Role of the Pesawaran Regency Election Supervisory Board (Bawaslu) in Overseeing the Neutrality of Civil Servants (ASN) in the 2024 Regional Head Election from the Perspective of Siyasah Tanfidziyyah - Dea Marisa; Frenki Frenki; Nurasari Nurasari (Asy-Syari’ah : Jurnal Hukum Islam, 2026)
This study aims to analyze the role and effectiveness of legal supervision carried out by the General Elections Supervisory Agency (Bawaslu) of Pesawaran Regency regarding the neutrality of State Civil Apparatus (ASN) in the implementation of the 2024 Regional Head Election (Pilkada), based on Article 4 Paragraph (1) Letter (a) of Bawaslu Regulation of the Republic of Indonesia Number 6 of 2018 concerning Supervision of the Neutrality of ASN Employees, Members of the Indonesian National Armed Forces (TNI), and Members of the Indonesian National Police (Polri). This study employs an empirical juridical method with a descriptive qualitative approach, using Siyasah Tanfidziyyah as the analytical framework. Data were collected through interviews, documentation, and a review of relevant laws and regulations. The results show that Bawaslu Pesawaran Regency has implemented supervision of ASN neutrality through socialization, letters of appeal, declarations of neutrality, coordination with related agencies, and direct supervision by the District Panwaslu. The level of violations of ASN neutrality in the 2024 Pilkada is relatively low, only one case was found, which indicates an increase in ASN awareness of the obligation of neutrality. However, the effectiveness of oversight is not yet fully optimal due to Bawaslu's limited authority to impose sanctions, weak follow-up on recommendations, time constraints, difficulties in providing evidence, and limited human resources. From a legal and administrative perspective, Bawaslu's role reflects efforts to uphold justice, ensure public trust, and ensure public welfare. Strengthening regulations, inter-agency coordination, and optimizing oversight authority are still needed to ensure the optimal implementation of Article 4 Paragraph (1) Letter (a), so that the principle of civil servant neutrality in the 2024 regional elections can be fully realized.